HERMAPHRODITISM IN A TELEOST, POLYNEMUS HEPTADACTYLUS CUV. AND VAL. - Kagwade, P V (Indian Journal of Fisheries, 2011)
In fishes reproduction is normally sexual by fertilization of male and female reproductive elements borne by individuals of the two separate sexes. However, certain reproductive specializations, viz. gynogenesis, parthenogenesis and hermaphroditism are at times met with. Gynogenesis is observed in Mollienesia formosa (Hubbs and Hubbs, 1932, 1946) which exclusively occurs as females, wherein during reproduction the sperms of a related species only stimulate the eggs but do not contribute to any genetic material and the resulting offspring are all females. Gynogenesis has also been observed in a cyprinid fish Carassius auratus gibelio (Lieder, 1955). Parthenogenesis or development of eggs without fertilization is very rare. Hermaphroditism, a condition in which both the male and female gametes are produced by the same individual, is very common in the lower animals but rare among the higher vertebrates. In teleosts it occurs either teratologically or normally or by the reversal of sex. Herrings, cods, mackerels, sardines and some of the Pleuronectidae exhibit teratological hermaphroditism. Some of the eels, symbranchids and member? belonging to the families Maenidae, Sparidae and Serranidae are normally hermaphrodites. A few members of these three families are subjected to sex reversal. Based on the nature of the ovotestis with respect to the maturing of the gamates, hermaphroditism can be classified into different groups. An ovotestis is said to be gonochoritic when only one of its sexes functions at a time depending on whether it is protandric or proterogynous. Self-fertilization is out of question here. D’Ancona (1945) has observed in Sparus auralies protandry where the male germ cells mature earlier than those of the female and in Diplodus spp. and other sparids, the presence of both testicular and ovarian parts in the same gonad, but only one of them attaining maturity. This condition presents a transition from hermaphroditism and is considered primitive to gonochorism.